The relationship of sit-to-stand tests with 6-minute walk test in healthy young adults. Issue 1 (January 2018) - Gurses, Hulya Nilgun; Zeren, Melih; Denizoglu Kulli, Hilal; Durgut, Elif
Abstract : Abstract: The aim of this study was to evaluate the timed sit-to-stand (STS) test performances of healthy young adults and to investigate the relationship of timed STS tests with 6-minute walk test (6MWT). A cross-sectional study was performed. A total of 40 healthy volunteers (mean age: 21.7 ± 1.2 years) were evaluated with 10, 30, and 60 seconds STS tests and 6MWT. Fatigue and shortness of breath were rated using Borg category-ratio scale (CR10) before and after each test. Weekly energy expenditures of volunteers were calculated using International Physical Activity Questionnaire. 30 and 60 seconds STS tests were moderately ( r  = 0.611 and r  = 0.647, respectively) ( P <  .001) and 10 seconds STS test was weakly ( r  = 0.344) ( P =  .028) correlated with 6MWT. Among correlations of each STS test with 6MWT, none of them was statistically stronger to one another ( P >  .05). Borg fatigue scores after 10, 30, and 60 seconds STS tests were weakly correlated with fatigue score after 6MWT ( r  = 0.321, r  = 0.378, and r  = 0.405, respectively) ( P <  .05). Weekly energy expenditure (MET-min/week) was moderately correlated with 10, 30, and 60 seconds STS tests and 6MWT ( r  = 0.533, r  = 0.598, r  = 0.598, and r  = 0.547, respectively) ( P <  .001). Considering the statistically significant relationship between timed STS tests and 6MWT, any of the timed STS tests may be used for a quick and alternative measurement of physical performance and functional capacity in healthy young adults.